Aerosol-Assisted Deposition for TiO2 Immobilization on Photocatalytic Fibrous Filters for VOC Degradation - Drdova, Sarka; Giannakou, Marianna; Jiang, Fuze; Lin, Luchan; Sivaraman, Deeptanshu; Toth, Rita; Graule, Thomas; Braun, Artur; Ilavsky, Jan; Kuzmenko, Ivan; Wang, Jing (Frontiers in Chemistry, 2022)
Atomization and spraying are well-established methods for the production of submicrometer- and micrometer- sized powders. In addition, they could be of interest to the immobilization of photocatalytic nanoparticles onto supports because they enable the formation of microporous films with photocatalytic activity. Here, we provide a comparison of aerosol-assisted immobilization methods, such as spray-drying (SD), spray atomization (SA), and spray gun (SG), which were used for the deposition of TiO2 dispersions onto fibrous filter media. The morphology, microstructure, and electronic properties of the structures with deposited TiO2 were characterized by SEM and TEM, BET and USAXS, and UV-Vis spectrometry, respectively. The photocatalytic performances of the functionalized filters were evaluated and compared to the benchmark dip-coating method. Our results showed that the SG and SA immobilization methods led to the best photocatalytic and operational performance for the degradation of toluene, whereas the SD method showed the lowest degradation efficiency and poor stability of coating. We demonstrated that TiO2 sprays using the SG and SA methods with direct deposition onto filter media involving dispersed colloidal droplets revealed to be promising alternatives to the dip-coating method owing to the ability to uniformly cover the filter fibers. In addition, the SA method allowed for fast and simple control of the coating thickness as the dispersed particles were continuously directed onto the filter media without the need for repetitive coatings, which is common for the SG and dip-coating methods. Our study highlighted the importance of the proper immobilization method for the efficient photocatalytic degradation of VOCs.